OPTIMIZATION OF ANTIOXIDANT ACTIVITY OF 96% ETHANOL EXTRACT OF Chromolaena odorata L. ABTS RADICAL PROPHYLACTIC - Usman, Yuri Pratiwi Utami; Rahmah Mustarin; Imrawati; Nurzadrina Wahyuddin; Suhaera; Besse Yuliana (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Choromolaena odorata L. is one of the plants used as an antioxidant. This research aims to determine the optimization of the antioxidant activity of 96% ethanol extract of C. odorata L. leaves using the ABTS method, a variety of drying techniques. Previous research has tested antioxidant activity using one drying technique, whereas this research uses a variety of drying techniques because the sample drying technique will affect its activity. Simplicia is obtained from various drying techniques. Then the simplicia was organoleptically tested and its water content was measured using the distillation method. The ethanol extract of Tacklean leaves was carried out using the maceration method using 96% ethanol solvent, then phytochemical screening was carried out using the TLC method and the antioxidant activity test of the ethanol extract of C. odorata L leaves was carried out using the ABTS method. The formation of the ABTS radical cation [2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) forms the basis of one of the spectrophotometric methods that has been applied to the measurement of total antioxidant activity of plants. The research results from the three drying techniques (50°C oven, direct sun drying, and air drying) showed organoleptic results in successive colors (brown, chocolate and dark green), while for shape and odor, namely dry leaves and a distinctive odor. The water content of simplicia ranges from 7.52-9.31%, soaked extract 8.4-10.3% and IC50 23.287-29.064 µg/mL and quarcetin as a comparison with IC50 2.292 µg/mL. Phytochemical screening results contain alkaloids, flavonoids, steroids and tannins. Oven drying at 50°C produced the greatest antioxidant activity with an IC50 value of 23.287 µg/mL which indicates very strong antioxidant power, although the antioxidant activity with a variety of drying techniques was all in the very strong category because it was <50 µg/mL.